1999
DOI: 10.1103/physrevlett.83.3860
|View full text |Cite
|
Sign up to set email alerts
|

Bi-state SuperfluidH3eWeak Links and the Stability of JosephsonπStates

Abstract: We have discovered new features of the current-phase relation, I͑f͒, in superfluid 3 He weak links. Firstly, we find that at any given temperature there are two distinct I͑f͒ functions that characterize the weak link. Secondly, both functions continuously develop an unusual form that ultimately leads to the previously reported p state. The observed form of I͑f͒ has recently been predicted for unconventional quantum fluids such as 3 He, high-T c superconductors, and Bose-Einstein condensates. The two distinct s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 24 publications
(33 reference statements)
2
49
0
Order By: Relevance
“…We consider this explanation unlikely because apparently the apertures in Ref. [5] are not hysteretic, and also because it is difficult to understand why exactly half of the apertures could behave differently. The second alternative is that the π state appears trivially in a coherent array if an isotextural π state appears in each of the apertures independently.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We consider this explanation unlikely because apparently the apertures in Ref. [5] are not hysteretic, and also because it is difficult to understand why exactly half of the apertures could behave differently. The second alternative is that the π state appears trivially in a coherent array if an isotextural π state appears in each of the apertures independently.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper we study superfluid 3 He, where the Josephson effect was experimentally confirmed over ten years ago by Avenel and Varoquaux [2,3]. However, more recent experiments in Berkeley have raised new questions [4,5] which we are going to address here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The former case resembles the Kulik-Omel'yanchuk result (2): at high temperatures I(φ) is sinusoidal but at lower tem- FIGURE 5. Measured current-phase relationships for a 65 × 65 array of 100 nm diameter apertures in 50 nm thick wall [16].…”
Section: Isotextural Theorymentioning
confidence: 99%
“…This could dress our dynamic π states from oscillations of the density depression at pores, producing fine structure in the oscillation modes. In fact, bistability between two types of π oscillations has been reported [21].…”
Section: Phase Equationmentioning
confidence: 99%